Traduções e torções ou o que se quer dizer quando dizemos queer no Brasil? - Silva, Larissa Maués Pelúcio [UNESP] (My University, 2014)
Since its arrival in Brazil at the beginning of the new century, queer theory – and particularly that variant of it linked to the works of Judith Butler – has been followed, criticized, contested and yet hardly problematicized in its deeper epistemological implications. Although Brazilian scholars have employed meanings and consistent debates regarding the changes that this axis of subaltern knowledge has provoked, there are still few discussions which seek to think about these contributions in the specific Brazilian context, in which categories of gender, sexuality, race and ethnicity link and cross in unique ways, creating experiences that are quite different from those generally discussed by foreign queer theorists. In the present article, I am trying to provoke an anthropophagic reflection, seeking fruitful dialogues with feminisms and post-colonial texts, emphasizing those that focus upon Latin-American reality, in an attempt create tension in our productions – thought in terms of local realities – as these face questions and issues that are also transnational. The idea here is to go beyond translating "queer", towards thinking of a theory informed by these productions, but which also dares to invent itself through questioning our own marginalized experience. In the present article, I look at the short but intense production of Argentine anthropologist Néstor Perlongher, taking it as one of the starting points for the elaboration of a Latin American (but mainly Brazilian) "teoria cu": that which is produced outside of the phallocentric and heteronormative regimes of canonic science.

Tras haber llegado en Brasil, en el comienzo de este siglo, marcadamente por medio de la obra de la filósofa Judit Butler, la teoría queer ha sido asimilada, criticada, contestada y poco problematizada de manera más profundizada acerca de sus implicaciones epistemológicas. Aunque que se haiga, nacionalmente, desarrollado significativos y consistentes debates acerca de los aportes que esta vertiente de los saberes subaltenizados ha provocado, aún son pocas las discusiones las cuales buscan pensar en estas contribuciones en el contexto específico brasileño, en cuyo marco las categorías de género, sexualidad, raza/etnia se interconectan de manera singular, performando experiencias muy distintas de aquellas tratadas por autoras y autores extranjeros comprometidos con el queer. La provocación en este artículo es de pensar antropofágicamente, intentando en esta investigación diálogos fructíferos con el feminismo, las lecturas post-coloniales, con énfasis en aquellas formuladas a partir de la realidad latinoamericana, intentándose tensionar nuestras producciones frente a cuestiones que son transnacionales. Más que traducciones para el "queer", la idea es pensar una teoría informada por estas producciones, pero que aventúrese a inventarse a sí misma a partir de nuestra experiencia marginal. En este articulo, tomo la corta pero intensa producción del antropólogo argentino Néstor Perlongher como uno de los marcos para la elaboración de una "teoría cu" latinoamericana, con énfasis en las discusiones brasileñas.

Desde que aportou no Brasil no início deste século, sobretudo via obra da filósofa Judith Butler, a teoria queer tem sido seguida, criticada, contestada e pouco problematizada em suas implicações epistemológicas mais profundas. Ainda que se tenha, nacionalmente, empreendido significativos e consistentes debates sobre os aportes que esta vertente dos saberes subalternizados tem suscitado, ainda são poucas as discussões que procuram pensar nessas contribuições no contexto específico brasileiro, no qual as categorias de gênero, sexualidade, raça/etnia, se interconectam de maneira singular, configurando experiências muito distintas daquelas discutidas por autoras e autores estrangeiros filiados a esta corrente. A provocação aqui é de pensar antropofagicamente, buscando nessa reflexão diálogos frutíferos com os feminismos, as leituras pós-coloniais, com ênfase naquelas pensadas a partir da realidade latinoamericana, na tentativa de tencionar nossas produções – pensadas a partir de realidades locais – diante de questões que também são transnacionais. Mais que traduções do "queer", a ideia aqui é pensar em uma teoria informada por essas produções, mas que ouse se inventar a partir de questões próprias de nossa experiência marginal. Nesta apresentação, tomo a curta, mas intensa, produção do antropólogo argentino Néstor Perlongher como um dos marcos para a elaboração de uma "teoria cu" latino-americana, mas, sobretudo brasileira, aquela produzida fora dos regimes falogocêntricos e heteronormativos da ciência canônica.
Keywords: Queer theory; Cu theory; South epistemology; Néstor Perlongher; Teoria queer; Teoría cuier; Epistemologías del sur; Néstor Perlongher; Teoria queer; Teoria cu; Epistemologias do sul; Néstor Perlongher